KELAYAKAN TEORITIS BAHAN AJAR BIOLOGI BERBASIS CTL MATERI SISTEM INDERA KELAS XI SMA - RAHMAH, MAZIDATUR (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
Teaching materials on the topic of Sensory System that used in the school only focus on the mastery of concepts,not build students’ attitudes and skill processes. The purpose of this research were to produce a worthy biological teaching material for Senior High School students on the topic of Sensory System usingContextual Teaching and Learning (CTL) approach which is proper if observed from the theoretical advisability. This research was a developmental research which was done using 4D model. This research’s target was teaching materials of biology based on CTL in Sensory System topic. The research result showed that the advisability of teaching materials which is obtained consist of the CTL component, content , language, and the presentation got average worthiness value about 3,5 – 4 valid to very valid criteria. Keywords: teaching material, Contextual Teaching and Learning (CTL), Sensory System